Integration of Faith, Knowledge, and Charity: A Novel Framework for Combating Academic Contract Cheating in Indonesian Universities - Darda, Abu; Nisa, Fathimah Kamilatun; Sari, Irma Lupita; Yoranita, Angelica Silfana Prisca; Hanifah, Isnaini Amirotun (Institut Agama Islam Negeri (IAIN) Manado, 2024)
The condition of academic integrity in Indonesia is currently facing serious challenges with the rampant practice of jockeying in the world of education. This phenomenon threatens the principles of honesty and responsibility that should be the main foundation in the learning process. The purpose of this study is to comprehensively analyze the role of the integration of the concepts of faith, knowledge and charity in revitalizing the pillars of academic integration in the midst of rampant jockeying practices. This research uses library research. The data collection technique uses the content analysis method by searching literature from various sources. Theoretically, this research can enrich the literature on academic integrity by integrating the concepts of faith, science, and charity, which provides a new perspective in understanding the relationship between religious principles and academic behavior. Based on this research, it is found that through the cultivation of spiritual values (faith), strengthening of understanding and correct knowledge ( ilān ), and the application of real actions ( amal ) in the learning process, it is expected that unethical practices such as jockeying can be minimized. Thus, education in Indonesia can return to its original essence, which is to produce a generation that is not only intellectually intelligent, but also has strong character and integrity. strong character and high integrity.